Economic evaluation of cattle management in the system of organic farming - I. Živělová; J. Jánský; P. Novák (Agricultural Economics (AGRICECON), 2003)
This paper introduces partial results of the research project QC 1140 aimed at the efficiency of enterprises operating in the system of organic farming, especially considering the use of grassland linked with cattle management. Economic evaluation of cattle management in the system of organic farming is compared with conventional enterprises. Economic evaluation applies to dairy cattle and beef cattle. Proposals of the measures will be formed with respect to the results of analysys, which should contribute to the support of organic enterprises and to better satisfaction of the increasing demand for organic food.